Education on Low Sodium Diets for Blood Pressure Control in Post-Partum Mothers With Superimposed Preeclampsia - Nicoletha Trudy Abya Karyo; Yanti Hermayanti; Ermiati Ermiati (Journal of Nursing, 2026)
Pre-eclampsia is closely related to postpartum hypertension, making it a critical period during which mothers are at risk of more serious complications if they do not receive immediate treatment. Its management requires adherence to lifestyle modifications, including a low-salt diet, in addition to medication control. Adherence is related to knowledge, so education is one of the non-pharmacological techniques that can be provided. This study aims to describe behavioural changes in patients with superimposed pre-eclampsia through the provision of low-salt diet education for blood pressure control. This study used a case study method through the nursing care process for a 42-year-old postpartum mother P5A2. Data were obtained through anamnesis, observation and physical examination, as well as documentation of diagnostic tests. Health education was implemented using lectures and question-and-answer sessions. Evaluation was assessed using pre-post tests, records of food consumption, and blood pressure measurements over 3 days. After receiving education, the blood pressure range decreased by -1 mmHg in systolic pressure and -13 mmHg in diastolic pressure on the second day compared to the first day, and -5 mmHg in systolic pressure and -15 mmHg in diastolic pressure on the third day compared to the second day. There was an increase in knowledge related to low-salt diets, which triggered behavioural changes in controlling daily intake, resulting in a decrease and stabilisation of blood pressure to a more controlled range. However, participants' understanding did not reach 100%, so demonstration methods are needed in health education to optimize participants' understanding.